Gandhian strategies for democratic decentralisation and development: dimensions on rural development, Gram Swaraj and Sarvodaya - Sharma, Sanjeev K.; Singh, Sarbjeet (2008)
Decentralisation of Political and economic power provides for the working of democracy based upon individual freedom and initiative, and for the individual being allowed to participate in the government of the country. it would also regulate automatically both the production and the distribution of the commodities necessary to human life, and both the production and the consumption of these would be in the same locality rather than having production concentrated in particular area only, thus necessitating regulations for the distribution of products and wealth. Decentralisation would also bring about the regulation of the use of machinery. The present unchecked use of machinery for selfish purpo ses has caused, for a large proportion of the people, a life of monotony and drudgery. - Reproduced.
Keywords: Gandhi, M.K.; Sarvodaya; Rural development; Decentralization